An in Silico Study of the Cathepsin L Inhibitory Activity of Bioactive Compounds in Stachytarpheta jamaicensis as a Covid-19 Drug Therapy - Utami, Juliyatin Putri; Kurnianingsih, Nia; Faisal, Mohammad Reza (Makara Journal of Science, 2022)
Inhibition of cathepsin L (Cat L) can be considered a target for COVID-19 treatment. Starchytapheta jamaicensis is a plant from the Verbenaceae family that is commonly used for medicinal purposes. This study aims to analyze the inhibitory activities of compounds of Stachytarpheta jamaicensis toward Cat L by computational docking analysis. Ten compounds contained in the extracts (i.e., α-spinasterol, apigenin, luteolol-7-glucuronide, friedelin, hispidulin, chlorogenic acid, ipolamiide, geraniol, hentriacontane, and γ-aminobutyric acid) were selected as ligands; decanoyl-arg-val-lys-arg-chloromethylketone and oxocarbazate were used as the reference. Computational docking analysis was performed using Autodock Vina integrated into PyRx 8.0 and visualized using the Discovery Studio Visualizer v19.1.0.18287 (2019 version) based on the scoring functions. Seven bioactive compounds were bound more strongly than decanoyl-arg-val-lys-arg-chloromethylketone: α-spinasterol, apigenin, luteolol-7-glucuronide, friedelin, hispidulin, chlorogenic acid, and ipolamiide. However, all bioactive compounds were bound with less strength than oxocarbazate. Apigenin showed the best affinity, with much hydrogen bonding, and had the same ASN18 residue as Cat L inhibitor 1. PreADMET showed that all compounds of S. jamaicensis did not have hepatotoxicity, mutagenic, and carcinogenic criteria. The current research indicates that S. jamaicensis compounds can be used as an inhibitor for Cat L and as a COVID-19 drug candidate.